Integrating AI-Powered Writing Assistant into English Essay Writing: Students’ Reflections and Challenges - Siti Hanna Sumedi; Fheby Indriyanti Nurpratiwi; Musiam Rianti (ELLITE: Journal of English Language, Literature, and Teaching, 2026)
This study explored the integration AI-powered writing assistant tool into English Essay Writing. Likewise, this study applied Narrative Inquiry design exploring two students’ reflections and challenges at a private university in Indonesia toward the integration of Jenni AI into English Essay Writing. The data were collected through Reflective journal and Interview. The data were analyzed thematically following Braun & Clark’s thematic analysis procedures. This study revealed students’ reflections and challenges of integrating Jenni AI into English Essay Writing. In terms of reflections, Jenni AI could value as a tool to improve students’ linguistic and discourse knowledge of writing. Likewise, it helps students in the aspects of writing efficiency enhancement. However, the challenges, Jenni AI leads to an ethical consideration in which reduced writing quality of students’ unique and creative styles of Essay writing. In this case, Jenni AI could make students become over-reliant. Hence, this study highlighted the importance of integrating Jenni AI as a helper not a replacement in Essay Writing since writing is a human-centered activity. Although it helps students in the matter of writing process and performance, but it is also affecting writing production that lessen students’ personal styles, uniqueness, creativity in Essay writing.